Clinical Significance of Induction of Atrial Fibrillation after Pulmonary Vein Isolation - Stychynskyi, Oleksandr S.; Almiz, Pavlo O.; Topchii, Alina V. (Ukrainian Journal of Cardiovascular Surgery, 2022)
Pulmonary vein isolation is a standard for catheter treatment of atrial fibrillation (AF). As for the need for additional impact on the arrhythmogenic substrate in the atria, there is no consensus or unified technique. The aim. To study the efficiency of AF induction by frequent atrial pacing as a prognostic criterium for arrhythmia recurrence in the long term after catheter treatment. Materials and methods. We analyzed 55 catheter procedures of AF ablation in 55 patients (27 women, mean age 52 ± 6.8 years) without structural heart disease. There were 28 patients and 27 patients with paroxysmal and persistent arrhythmia, respectively. Concomitant diseases (coronary heart disease, hypertension, diabetes) were reported in 30 (54.5%) cases. The technique of the procedure was as follows. At first, the pulmonary veins were isolated. After that frequent stimulation was carried out from two sites with a cycle of 300 ms for 10 seconds, with a phased shortening by 20 ms, until atrial refractoriness was achieved. Arrhythmia was considered induced if its episode lasted more than 30 seconds. In case of induction of AF and absence of its spontaneous termination within the pre-specified time, the search and ablation of the areas with fragmented activity were performed. There were no additional effects on the substrate in the atria. Recurrence of AF was defined as the occurrence of AF within 3 months after ablation. Results. Atrial fibrillation was induced in 9 (16.4%) of 55 patients. During the follow-up period lasting 12 to 26 months, recurrent arrhythmia occurred in 11 (20%) of 55 patients, including 3 (33.3%) of 9 with induced AF, and 8 (17.4 %) of 46 in whom it was not induced (relative risk 1.9; odds ratio 2.4; 95% confidence interval 16.5-23.5). Comparison of the recurrence rate depending on the form of arrhythmia did not reveal significant differences: the relative risk was 2.2 for persistent form and 1.5 for paroxysmal form (P > 0.05). Conclusions. Our results indicate that in cases where AF was induced after pulmonary vein isolation, the likelihood of its subsequent recurrence was twice as high as in cases when it was not induced. This trend was observed both in paroxysmal and persistent forms of arrhythmia.